The Establishment of the Jute Industry: A Problem of Location Theory? - Chapman, Dennis (Review of Economic Studies, 1938)
Journal Article The Establishment of the Jute Industry: A Problem of Location Theory? Get access Dennis Chapman Dennis Chapman St. Andrews Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 6, Issue 1, October 1938, Pages 33–55, https://doi.org/10.2307/2967537 Published: 01 October 1938